2006
DOI: 10.1111/j.1365-2929.2006.02503.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of medical student reactions to feedback: a randomised controlled trial

Abstract: Student satisfaction is not an accurate measure of the quality of feedback. It appears that satisfaction ratings respond to praise more than feedback, while learning is more a function of feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
1
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(156 citation statements)
references
References 25 publications
6
141
1
8
Order By: Relevance
“…Communication and feedback from preceptors has been found to increase skills, 27 confidence, 28 knowledge, 27,28 self-esteem, 28 productivity, 28 clinical performance, 28,29 and professional behavior. 28 Program administrators should encourage and promote this interaction to improve the professional communication skills of their students.…”
Section: Discussionmentioning
confidence: 99%
“…Communication and feedback from preceptors has been found to increase skills, 27 confidence, 28 knowledge, 27,28 self-esteem, 28 productivity, 28 clinical performance, 28,29 and professional behavior. 28 Program administrators should encourage and promote this interaction to improve the professional communication skills of their students.…”
Section: Discussionmentioning
confidence: 99%
“…10 La observación concluye con una instancia de devolución constructiva o feedback que el evaluador debe aprovechar para dar recomendaciones, promover la autorreflexión identificando áreas por corregir y definiendo un plan de acción que contribuya a mejorar las habilidades del estudiante. 11,12 Su principal ventaja radica en que permite realizar evaluaciones en situaciones clínicas reales, cotidianas, de variada complejidad y en distintos ámbitos, a la vez que resulta un buen complemento para otros instrumentos utilizados que evalúan solo conocimiento y razonamiento (preguntas de elección múltiple, simuladores, etc.). …”
Section: Introductionunclassified
“…However, the feedback students appreciate is not necessarily the feedback that best supports their learning. For example, Boehler et al (2006) found not only that general praise led to improved student satisfaction ratings when compared with constructive feedback, but also that these more satisfied students failed to improve their performance compared with their less satisfied peers. Focusing more on student learning than student satisfaction means questioning the assumption that the customer is always right .…”
Section: Feedback In Academic Writing Support Servicesmentioning
confidence: 99%